Intercultural Communication (2016)
In the Colombian educational context when a language is taught specifically English, certain important factors that support the teaching learning process in an optimal way are discriminated, one of those important elements are the intercultural communication competences. This research addresses to an optimal methodology towards intercultural communication in a university context in order to improve the speaking skills. This implementation has left a way to rise students with a more complete learning process of a language, it shows the importance that has to instruct not only the linguistic part of the language but also the cultural part that comes with that target language.